Variation in Meteorological Parameters Over Pakistan during April 2014 - Jahanzeb Qureshi; Amer Masood; Waqas Shafi; M. Abrar Hussain; Syed Amer Mahmood (Journal of Basic & Applied Sciences, 2017)
In this study we investigated the meteorological data comprising temperature, dew point, humidity and mean sea level for four major cities of Pakistan (Karachi, Multan, Lahore and Peshawar) on varying latitudes from 25°N to 34°N. These cities are selected to study the variation of coastal, southern, central and northern parts of Pakistan and different variations are observed in ranges i.e difference between lowest and highest values. A clear variation in ranges of meteorological parameters are investigated for these cities to validate this research. This variation in meteorological parameters is because of climate change due to flow of high moisture laden winds from Arabian sea towards Karachi coast in the south. The results obtained regarding dew point temperature, moisture content and atmospheric pressure in the southern city of Karachi represent low values instead of high. As a result, Karachi has different climatic patterns as a coastal city than other areas which are continental in climatic effects.